2023
DOI: 10.3389/fmed.2023.1132695
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant organism-peritoneal dialysis associated peritonitis: clinical and microbiological features and risk factors of treatment failure

Abstract: BackgroundMultidrug-resistant (MDR) bacterial infection causes difficulty in the therapy of peritoneal dialysis-associated peritonitis (PDAP); however, there are few studies on multidrug-resistant organism (MDRO)-PDAP. In view of growing concerns about MDRO-PDAP, the aim of this study was to investigate the clinical features, risk factors of treatment failure, and causative pathogens of MDRO-PDAP.MethodsIn total, 318 patients who underwent PD between 2013 and 2019 were included in this multicenter retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The relationship between PD duration and peritonitis prognosis has been widely discussed. Previous studies have shown that PD duration was significantly associated with treatment failure and was an independent risk factor for poor prognosis in peritonitis [ 6 , 24 ]. With the extension of PD duration, the peritoneum is continuously exposed to non-biocompatible glucose-based dialysis solution, which results in a change in peritoneal morphology and impaired function [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between PD duration and peritonitis prognosis has been widely discussed. Previous studies have shown that PD duration was significantly associated with treatment failure and was an independent risk factor for poor prognosis in peritonitis [ 6 , 24 ]. With the extension of PD duration, the peritoneum is continuously exposed to non-biocompatible glucose-based dialysis solution, which results in a change in peritoneal morphology and impaired function [ 25 ].…”
Section: Discussionmentioning
confidence: 99%